Fabrication of alpha-tocopheryl acetate-loaded nanoemulsion towards cosmetic application - Vuong Khanh Hoang,; Vo Le Tuong Van,; Doan Tran Buu Le,; Ton Tan Phuoc,; Dang Le Hang,; Nguyen Dinh Trung,; Quyen, Tran Ngoc (Vietnam Journal of Science and Technology, 2024)
Recently, fabrication of nanoemulsion has drawn substantial interest in the field of pharmaceutical chemistry, particularly the development of nanosystems for the delivery of bioactive compounds. The idea of this material is to encapsulate and carry water-insoluble active agents to the targeted site. Our work focuses on the ideal delivery system for alpha-tocopheryl acetate (AVE), which currently covers a broad range of medications, supplementation and cosmetics. To put it in detail, we investigated different kinds of pluronic emulsifiers (pluronic F127, pluronic P123 and their mixture) to fabricate the AVE-loaded nanoemulsion particles. The structure, physicochemical properties, stability and biocompatibility of various formulations were compared using Fourier-transform infrared spectroscopy (FT-IR) spectra; Dynamic light scattering (DLS); macroscopic and microscopic images; Transmision electron microscopy (TEM) and in vitro cytotoxicity test. The obtained results exhibited a high stability of AVE-loaded pluronic mixture as compared to that of the free-AVE sample. Moreover, the dual pluronic formulation also showed a great cytocompatibility which could be utilized in topical and transdermal delivery.